Efficacy of abdominal trunk muscles-strengthening exercise using an innovative device in treating chronic low back pain: a controlled clinical trial - Kitagawa, Ryo (Sci Rep, 2020)
Exercise is the most common conservative intervention for chronic low back pain (CLBP). We have developed an innovative exercise device for the abdominal trunk muscles that also measures muscle strength in a sitting position. The device, which is easy for patients with CLBP to use, allows for lumbar stabilization exercise under pressure. This study aimed to examine the efficacy of abdominal trunk muscle strengthening using the device in improving CLBP. We conducted a two-group non-randomized controlled clinical trial. CLBP patients were allocated into two groups. The strengthening group underwent a 12-week exercise program that included abdominal trunk muscle strengthening using our device and stretching exercises, while the control group received a 12-week stretching exercise program. The outcome measures included the improvement of the abdominal trunk muscle strength measured by the device, pain intensity of CLBP, physical function, and quality of life (QOL). A total of 40 participants (20 in each group) were analyzed. The strengthening group showed better improvement in the abdominal trunk muscle strength, CLBP, physical function, and QOL than in the control group. In conclusion, the strengthening exercise using the device with easy stretching was effective in improving the strength of the abdominal trunk muscles, pain intensity of CLBP, physical function, and QOL.